2019
DOI: 10.1111/ina.12535
|View full text |Cite
|
Sign up to set email alerts
|

Collection efficiency of liquid‐based samplers for fungi in indoor air

Abstract: This study assessed the collection efficiency (CE) of two popularly used sampling devices (BioSampler and Coriolis sampler) for fungal aerosols. Phosphate‐buffered saline (PBS) supplemented with or without surfactant (Tween‐20, Tween‐80, or Triton X‐100) and antifoam agent was prepared and used as collection liquids. The agar impactor (BioStage) was simultaneously operated with liquid‐based samplers to collect fungi from seven sites located at a university building, public library, and animal farming. Fungal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
(74 reference statements)
1
16
0
Order By: Relevance
“…Liquid loss during air sampling is known to occur with traditional impingers ( Willeke et al , 1998 ; Han and Mainelis, 2012 ) and has also been reported for the Coriolis ( Carvalho et al , 2008 ; Chang et al , 2019 ). During impingement, liquid loss may be coupled to the escape and reaerosolization of material from the collection media ( Grinshpun et al , 1997 ; Riemenschneider et al , 2010 ; Han and Mainelis, 2012 ).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Liquid loss during air sampling is known to occur with traditional impingers ( Willeke et al , 1998 ; Han and Mainelis, 2012 ) and has also been reported for the Coriolis ( Carvalho et al , 2008 ; Chang et al , 2019 ). During impingement, liquid loss may be coupled to the escape and reaerosolization of material from the collection media ( Grinshpun et al , 1997 ; Riemenschneider et al , 2010 ; Han and Mainelis, 2012 ).…”
Section: Introductionmentioning
confidence: 91%
“…The Coriolis has tactical capacity and produces a sample that is amenable to different analytical methods. It is gaining ground as a tool for microbiological air sampling where it has been successfully used to detect toxins or microbial contaminants in the food industry ( Verreault et al , 2011 ; Viegas et al , 2012 , 2014 ; Ahmed et al , 2013 ; Chang et al , 2019 ), fungus and pollen in outdoor and indoor air ( Carvalho et al , 2008 ; Gómez-Domenech et al , 2010 ; Chang et al , 2019 ) and airborne pathogens in healthcare facilities ( Choukri et al , 2010 ; Bellanger et al , 2012 ; Le Gal et al , 2015 ; Montagna et al , 2017 ; Alsved et al , 2019 ; Montagna et al , 2019 ). In the above studies the Coriolis was used mainly in conjunction with culture and nucleic acid amplification methods, although microscopy and in some cases spoligotyping and sequencing were also performed.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, microorganisms grow in a liquid medium, such as spilled product, rinse water or wastewater, which subsequently becomes aerosolized. Microorganisms may also be suspended as such in the air after dissipation or evaporation or as "passengers" on solid dust particles (e.g., hair, clothing fiber, skin), which are dispersed in a food processing unit (Chang, Ting, & Horng, 2019;Heo, Lim, Kee, & Lee, 2017). Microorganisms in the air may settle on food products, equipment, containers and other food contact surfaces during handling (Brandl et al, 2014).…”
Section: What Is a Bioaerosol And Why Air Monitoring Is Important?mentioning
confidence: 99%
“…The contribution of airborne microorganisms to food contamination has been addressed (Chang, et al, 2019;Chen et al, 2019;Shale & Lues, 2007). Burfoot and Brown (2004) reported that the ratio of microorganisms to total particles may range up to more than two orders of magnitude.…”
Section: What Is a Bioaerosol And Why Air Monitoring Is Important?mentioning
confidence: 99%
“…In regards to the technical aspects, a recent study showed that the use of the Coriolis ® collector may underestimate the number of CFU for fungal spores [46]. This could mean that the fungal concentration recorded in our study may be below the real concentration of these fungal species in air.…”
Section: Discussionmentioning
confidence: 65%